2017
DOI: 10.2337/db17-0356
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From Adipose-Derived Stem Cells Attenuate Adipose Inflammation and Obesity Through Polarizing M2 Macrophages and Beiging in White Adipose Tissue

Abstract: Adipose-derived stem cells (ADSCs) play critical roles in controlling obesity-associated inflammation and metabolic disorders. Exosomes from ADSCs exert protective effects in several diseases, but their roles in obesity and related pathological conditions remain unclear. In this study, we showed that treatment of obese mice with ADSC-derived exosomes facilitated their metabolic homeostasis, including improved insulin sensitivity (27.8% improvement), reduced obesity, and alleviated hepatic steatosis. ADSC-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
391
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(408 citation statements)
references
References 51 publications
16
391
0
1
Order By: Relevance
“…However, Lipo‐NPs caused substantial reduction in inflammatory cytokines, including interleukin 1 alpha (IL1α), IL‐6, and TNF‐α, which was further enhanced by GBZ loading (Figure 7D). Similar reductions in inflammatory cytokines have previously been noted in response to ADSC EVs, particularly with TNF‐α33 and IL‐6 67. Lipo‐NPs alone did not reduce the levels of GM‐CSF, but Lipo‐NPs loaded with GBZ did (Figure 7D).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, Lipo‐NPs caused substantial reduction in inflammatory cytokines, including interleukin 1 alpha (IL1α), IL‐6, and TNF‐α, which was further enhanced by GBZ loading (Figure 7D). Similar reductions in inflammatory cytokines have previously been noted in response to ADSC EVs, particularly with TNF‐α33 and IL‐6 67. Lipo‐NPs alone did not reduce the levels of GM‐CSF, but Lipo‐NPs loaded with GBZ did (Figure 7D).…”
Section: Resultssupporting
confidence: 79%
“…Previous studies have demonstrated that MSC‐EVs contain biomolecular cargo with anti‐apoptotic and anti‐oxidant effects. For example, miR‐2133 and miR‐12639 were shown to decrease cellular apoptosis through, e.g., the phosphatase and tensin homolog (PTEN)‐protein kinase B (AKT) pathway. Moreover, glutathione peroxidase in MSC EVs was shown to decrease oxidative stress in cells 40.…”
Section: Resultsmentioning
confidence: 99%
“…M2-like macrophages are traditionally associated with wound healing, but investigators have considered their anti-inflammatory phenotype to promote appropriate glucose and lipid control in WAT as well [43]. The M2-like phenotype of WAT macrophages is sustained through transcriptional activators such as PPARs, microRNAs such as miR-330-5p [69], adipose-derived stem cells [70], and cytokines such as IL-4 and IL-13 [32,[71][72][73][74]. Due to their proximity, M2-like macrophages are thought to interact with adipocytes, and may play roles in apoptotic clearance, angiogenesis, WAT development, antigen presentation, and inflammatory resolution [reviewed in [26,75]].…”
Section: Counterpoint To the Proinflammatory Adipose Tissue Macrophagmentioning
confidence: 99%
“…Regarding T2D, treatment of obese mice with exosomes released by adipose tissue MSCs (AT‐MSCs) improved insulin sensitivity, reduced obesity, and alleviated hepatic steatosis by transferring active signal transducer and activator of transcription 3 (STAT3) and directing the alternative M2 activation of macrophages . Treatment with exosomes isolated from human umbilical cord MSCs (hucMSCs) was also able to increase insulin sensitivity and β‐cell survival in a rat model of T2D by combined high‐fat diet (HFD) feeding and STZ injection .…”
Section: Exosomes As Therapy For Diabetesmentioning
confidence: 99%